2010
DOI: 10.11144/javeriana.upsy9-2.ppve
|View full text |Cite
|
Sign up to set email alerts
|

Propiedades psicométricas de la versión en español de la escala revisada de restricción alimentaria en una muestra de adolescentes

Abstract: La escala de restricción revisada (ER) es un instrumento psicométrico para medir restricción alimentaria crónica. Objetivo: Obtener la fiabilidad y estructura factorial de la versión en español de la ER en una muestra de adolescentes. Materiales y método: 838 adolescentes (15,5 años) completaron el instrumento. Se realizó un análisis factorial exploratorio y confirmatorio sobre los puntajes. Resultados: Ambas sub-escalas de la ER muestran una fiabilidad apropiada, aunque el item 9 mostró una homogeneidad corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…Higher scores indicate stricter dietary restraint ( Lai et al, 2013 ). In this research study, the Spanish version of the RRS ( Silva, 2010 ) was used, which has shown adequate levels of internal consistency for each subscale (DC = 0.68–0.78, WF = 0.71–0.79) in previous studies conducted in Chile with female adolescents and undergraduate students ( Silva, 2010 ; Silva and Urzúa-Morales, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate stricter dietary restraint ( Lai et al, 2013 ). In this research study, the Spanish version of the RRS ( Silva, 2010 ) was used, which has shown adequate levels of internal consistency for each subscale (DC = 0.68–0.78, WF = 0.71–0.79) in previous studies conducted in Chile with female adolescents and undergraduate students ( Silva, 2010 ; Silva and Urzúa-Morales, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similar results were reported by Mak and Lai (2012) in a mixed gender sample of adolescents in Hong Kong, though the results indicated a three-factor structure on the RRS. Although the 10-item version of the RSS has been validated in Spanish-speaking female undergraduate students ( Silva, 2010 ) and adolescents ( Silva and Urzúa-Morales, 2010 ), to our knowledge, its psychometric properties have not yet been assessed in male and female adolescents. Therefore, the present study addresses the factor structure of the RRS and its psychometric properties in both male and female adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Las participantes acudieron al laboratorio y respondieron un set de instrumentos psicométricos así como una prueba conductual asociados a un estudio amplio en desarrollo. Se les clasifi có en dos grupos, dietante crónico o no dietante, aplicando la versión en español de la escala revisada de restricción alimentaria (ERA) [27][28][29] . La ERA es un auto-reporte que evalúa actitudes hacia la alimentación, frecuencia de dietas y fl uctuación de peso, permitiendo su clasifi cación de los participantes en dietantes crónicas y no dietantes (punto de corte de 12).…”
Section: Procedimientounclassified